Criminal proceedings after the Human Rights Act: The first year - Ashworth, A (2001)
The first part of the article reviews decisions in this country and in Strasbourg during the first year of the Human Rights Act, and the second part raises some more general issues about the way in which Parliament and the courts have approached the task of developing a British law of human rights. © Sweet and Maxwell.